2009
DOI: 10.1002/art.24701
|View full text |Cite
|
Sign up to set email alerts
|

Association of STAT4 and BLK, but not BANK1 or IRF5, with primary antiphospholipid syndrome

Abstract: Objective. Primary antiphospholipid syndrome (APS) is formally classified by the presence of antiphospholipid antibodies, recurrent thrombosis, and/or pregnancy morbidity in the absence of any underlying fullblown systemic autoimmune disease. However, systemic manifestations in patients with primary APS have been recently reported, as has the presence of serologic markers in common with systemic lupus erythematosus (SLE). In spite of similarities between the 2 diseases, only a minority of cases of primary APS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…16 A STAT4 risk allele has also recently been associated with the primary APS. 37 In summary, genetic variants within the type I IFN system (STAT4) associated with VD and IFN␣ mediated endothelial dysfunction all contribute to the pathogenesis of VD. The correlation found between type I IFN-regulated proteins and platelet activation markers demonstrated in this paper adds a novel mechanism for development of VD in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…16 A STAT4 risk allele has also recently been associated with the primary APS. 37 In summary, genetic variants within the type I IFN system (STAT4) associated with VD and IFN␣ mediated endothelial dysfunction all contribute to the pathogenesis of VD. The correlation found between type I IFN-regulated proteins and platelet activation markers demonstrated in this paper adds a novel mechanism for development of VD in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the significant association of both STAT4 and IRF5 polymorphisms has been also reported for other autoimmune diseases or inflammatory conditions, such as systemic sclerosis, 14 rheumatoid arthritis, 15 lupus. 8,11,[15][16][17][18] Interestingly, all these autoimmune diseases could be, to some extent type 1 IFN driven. This study provides additional data suggesting that STAT4 and IRF5 function independently on pSS genetic susceptibility, with an additive effect but with no epistatic interaction between both genes, which confirms the findings from Nordmark et al 6 in patients of North European ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…Abelson et al 8 reported a modest but significant correlation between STAT4 rs7574865 polymorphism (in complete LD with STAT4 rs7582694) and STAT4a mRNA level in PBMCs from 73 healthy volunteers. Sigurdsson et al 17 reported an increased expression of the risk allele of STAT4b in primary cells of mesenchymal origin (osteoblasts). None of the previous studies has addressed the functional consequences of STAT4 rs7582694 or STAT4 rs7574865 polymorphism among pSS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antiendothelial antibodies have been demonstrated in up to 50% of GCA patients [38]. Since an association between BLK and primary antiphospholipid syndrome was previously described [39], we aimed to determine whether a potential association of the C8orf13-BLK gene region with GCA might exist. However, in the present study, we could not confirm an association of GCA with rs13277113 and rs2736340 variants located within the C8orf13-BLK region.…”
Section: Discussionmentioning
confidence: 99%